2009
DOI: 10.3390/ph2020033
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of Some Prenylated Xanthones

Abstract: Pyranoxanthones 6-8 were obtained by dehydrogenation of the respective dihydropyranoxanthones 3-5 with DDQ in dry dioxane. Two prenylated xanthones 10,11 were obtained from the reaction of 1-hydroxyxanthone (9) with prenyl bromide in alkaline medium, or by condensation of xanthone 9 with isoprene in the presence of orthophosphoric acid. The structural elucidation of the two new compounds 6,11, as well as an update of data for the already described prenylated derivatives 7,8,10 were accomplished by IR, UV, HRMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 13 publications
0
31
0
Order By: Relevance
“…In many conditions, activities are associated with prenylation of the xanthone skeleton [5]. Various biological and pharmacological activities, such as antibacterial, antifungal, anti-inflammatory, antioxidant, and antitumor, have been reported for prenylxanthones, which make these compounds attractive for pharmaceutical applications [6]. …”
Section: Introductionmentioning
confidence: 99%
“…In many conditions, activities are associated with prenylation of the xanthone skeleton [5]. Various biological and pharmacological activities, such as antibacterial, antifungal, anti-inflammatory, antioxidant, and antitumor, have been reported for prenylxanthones, which make these compounds attractive for pharmaceutical applications [6]. …”
Section: Introductionmentioning
confidence: 99%
“…p-Sulfonic acid calix [4]arene has shown some interesting capabilities in preparation of conducting polymer, polyaniline, as a doping agent [37], encapsulating to topotecan for improving solubility in chemotherapy [38], and has bee proven to be suitable for bio-pharmaceutical applications [39].…”
Section: Resultsmentioning
confidence: 99%
“…Our research also indicated that pyranoxanthones could have more potent cytotoxic effects than previously discovered, as previous literature showed that prenylated xanthones had weak cytotoxicity (IC 50 values 50~ 80 μ M). 20 …”
Section: Cytotoxic Activitymentioning
confidence: 99%